COMPARATIVE STUDY OF INTRAVENOUS PARACETAMOL AND INTRAVENOUS DICLOFENAC ANALGESIA WITH RESPECT TO EFFECT ON RENAL FUNCTION, BLEEDING TIME, AND CLOTTING TIME IN POST-OPERATIVE CASES UNDERGOING LSCS UNDER SPINAL ANESTHESIA - JULIE PHILIPOSE BABY; ASHWINI MOTICHAND SHAH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aims and objectives of the study are to compare paracetamol and diclofenac for post-operative analgesia, efficacy, and safety profiles in patients undergoing LSCS under spinal anesthesia. Methods: Fifty-eight patients undergoing LSCS under spinal anesthesia were included in this study. Out of these 58 patients, 30 patients received paracetamol (Group P) and the remaining 28 patients received diclofenac (Group D). Post-operative pain was assessed using the Visual Analog Scale. Rescue analgesic used was buprenorphine intravenous at a dose of 1 mg/kg. Injection buprenorphine was given to the patient with a VAS score of more than three in addition to the routine dose of the study drug. Pre-operative and post-operative values of blood urea, serum creatinine, bleeding time, and clotting time were compared in both groups. p<0.05 were taken as statistically significant. Results: The mean age of patients in both groups was found to be comparable with no statistically significant difference (p=0.3849). In post-operative period at 150, 180 min, and 210 min, Group P reported significantly higher pain scores as compared to Group D with p-values indicating statistical significance (p<0.05). The analysis of pre- and post-operative renal function tests, bleeding time, and clotting time showed that there was no significant difference in the pre- and post-operative renal function tests, bleeding time, and clotting time of the patients in Group P and Group D. Conclusion: Intravenous diclofenac is found to have a superior analgesic effect as compared to intravenous paracetamol. Both paracetamol and diclofenac were found to have no significant side effects on renal functions, bleeding time, or clotting time.